Results of monitoring probable cases of acute severe hepatitis of unknown etiology in children in Мoscow in 2022 - М. А. Sayfullin; L. N. Mazankova; A. Yu. Rtischev; E. N. Abramova; N. A. Antypyat; N. N. Zvereva; O. A. Ivanova; M. A. Kolikova; A. A. Rakhalina; K. K. Rumyantseva; A. A. Samkov; I. N. Tyurin (Детские инфекции (Москва))
In the spring 2022, the number of cases of severe acute hepatitis of unknown etiology was unusual increased in Europe. As an immediate response, the World health organization recommended active efforts to identify such cases at the international level. For monitoring of acute hepatitis in Moscow, patients with suspected liver disease were sent to Infectious Diseases Clinical Hospital No. 1. The goal: study of the structure of diseases occurring with liver damage in children hospitalized in 2022. Materials and methods: analysis of medical records of children hospitalized with a diagnosis of hepatitis from May 1 to December 31, 2022. Еpidemiological data (age, gender, parenteral manipulations, contacts with patients, travel abroad), clinical (fever, jaundice, etc.), laboratory parameters were assessed. Results: A total of 164 completed cases of hepatitis in children aged 5 months to 17 years were analyzed. 36 children met the criteria for probable severe acute hepatitis of unknown etiology. Age median was 7 years [2.25;11]. Girls made up more than half (21 (58.3%). Non-infectious genesis was established in 15 (41.6%). The infectious disease was verified in 11 (30.5%), of which adenoviral infection was detected in 2 children. In 9 (25%) children the etiology of hepatitis was not established. Conclusion. Various infectious and non-infectious diseases among hospitalized children lead to a significant increase in liver transaminases. Most acute hepatitis with unspecified etiology proceeded as an acute infectious disease and ended in recovery. The role of adenoviruses in the development of severe hepatitis in children was not confirmed in our study.